2005
DOI: 10.1038/sj.jcbfm.9600202
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Storage Capacity in Caudate and Putamen of Patients with Early Parkinson's Disease: Correlation with Asymmetry of Motor Symptoms

Abstract: Conventional graphical analysis of positron emission tomography (PET) recordings of the cerebral uptake of the DOPA decarboxylase substrate [ 18 F]fluorodopa (FDOPA) assumes irreversible trapping of [ 18 F]fluorodopamine formed in the brain. However, 4-h long PET recordings allow the estimation of a rate constant for elimination of [ 18 F]fluorodopamine from the brain (k loss ), from which can be calculated an effective distribution volume (EDV 1 ), which is an index of [ 18 F]fluorodopamine storage capacity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 63 publications
2
26
0
Order By: Relevance
“…Increased uptake and decreased turnover of FDOPA in the basal ganglia following IFN-α administration are in stark contrast to that observed in patients with PD, where decreased uptake and increased FDOPA turnover are seen. Decreased uptake of FDOPA in PD is believed to be a function of the loss of DAergic neurons and/or their projections throughout the basal ganglia (Kaasinen et al, 2001;Kumakura and Cumming, 2009;Leenders et al, 1986), and intact or increased turnover suggests that the surviving neurons are capable of normal release (Kumakura and Cumming, 2009;Kumakura et al, 2006). Increased FDOPA uptake during IFN-α treatment suggests intact terminals that exhibit a potential depletion of DA and increased synthetic capacity.…”
Section: Neuroimaging Of the Da System And Corticostriatal Reward Cirmentioning
confidence: 99%
“…Increased uptake and decreased turnover of FDOPA in the basal ganglia following IFN-α administration are in stark contrast to that observed in patients with PD, where decreased uptake and increased FDOPA turnover are seen. Decreased uptake of FDOPA in PD is believed to be a function of the loss of DAergic neurons and/or their projections throughout the basal ganglia (Kaasinen et al, 2001;Kumakura and Cumming, 2009;Leenders et al, 1986), and intact or increased turnover suggests that the surviving neurons are capable of normal release (Kumakura and Cumming, 2009;Kumakura et al, 2006). Increased FDOPA uptake during IFN-α treatment suggests intact terminals that exhibit a potential depletion of DA and increased synthetic capacity.…”
Section: Neuroimaging Of the Da System And Corticostriatal Reward Cirmentioning
confidence: 99%
“…Increased uptake and decreased turnover of FDOPA in the basal ganglia following IFN-alpha administration is in stark contrast to that observed in patients with PD where decreased uptake and increased FDOPA turnover is found. Decreased uptake of FDOPA in PD is believed to be a function of loss of dopaminergic neurons and/or their projections throughout the basal ganglia [95, 111, 116], and intact or increased turnover suggests that the surviving neurons are capable of normal release [111, 112]. Increased FDOPA uptake during IFN-alpha treatment suggests a potential depletion of dopamine and increased synthetic capacity.…”
Section: Cytokine Effects On the Basal Ganglia And Dopamine-relatementioning
confidence: 99%
“…Other investigators have reported a greater reduction in striatal dopamine transporter binding contralateral to the more affected side of the body [15][16][17]. Further, the putamen and caudate contralateral to the more affected side of the body are associated with a reduced [ 18 F] dopa effective distribution volume and elimination rate [18]. Even when patients who had unilateral onset develop bilateral signs and symptoms these patients' motor and neuropathological asymmetries persist [19], with more severe extrapyramidal signs on the side of the body initially affected [20].…”
Section: Introductionmentioning
confidence: 99%